(untitled) (American Journal of Research in Humanities and Social Sciences, 2026)
This article examines the ecological problems of the Aral Sea region through the prism of the systemic-synergetic approach. The Aral Sea crisis is interpreted as a multi-level systemic phenomenon formed as a result of the complex interaction of ecological, economic, social, and demographic factors. Based on the key principles of systemic-synergetic methodology—open systems, self-organization, nonlinearity, bifurcation, and cooperation—the current condition and development prospects of the Aral Sea region are analyzed. Particular attention is paid to the theoretical and methodological foundations of ensuring environmental security, promoting a green economy, and strengthening regional cooperation.